Anlotinib Enhances the Therapeutic Effect of Bladder Cancer with GSDMB Expression: Analyzed from TCGA Bladder Cancer Database & Mouse Bladder Cancer Cell Line - Wang C; Cao Q; Zhang S; Liu H; Duan H; Xia W; Shen H; Wang C (Dove Medical Press, 2023)
Chen Wang,1,2 Qifeng Cao,2,* Shun Zhang,2,* Hailong Liu,2 Huangqi Duan,2 Weimin Xia,2 Haibo Shen,2 Cheng Wang1 1Department of Urology, The People's Hospital of SND, Suzhou, People's Republic of China; 2Department of Urology, Xinhua Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Cheng Wang, Department of Urology, The People's Hospital of SND, Suzhou, People's Republic of China, Tel +86-15050163288, Email 15050163288@163.com Haibo Shen, Department of Urology, Xinhua Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, People's Republic of China, Tel +86-18601712802, Email shenhaibo@xinhuamed.com.cnIntroduction and Objective: The mitogen-activated protein kinase (MAPK) pathway is inhibited by the pan-target inhibitor Anlotinib, which induces tumor cell death. In addition to the common apoptosis and necrosis, there is also a pyroptosis mode of cancer cell death in recent years, which is mainly manifested by the cleavage of gasdermin proteins (GSDMs). Gasdermin B (GSDMB) participates in the progression and outcome of bladder cancer. The efficacy and mechanism of Anlotinib in the treatment of GSDMB-positive bladder tumors have not been studied to date.Methods: The relationship between GSDMB expression and tumor stage, overall survival rate, immunotherapy response, tumor recurrence and progression rate was analyzed from the TCGA bladder cancer database. Anlotinib was used to treat GSDMB-positive bladder cancer in mice followed by flow analysis of the secretion of inflammatory factors related to pyroptosis and the level of anti-tumor factors. Western blot analysis detected which MAPK and MEK signal transduction pathways.Results: TCGA data analysis showed that the overall survival rate of bladder cancer patients with high GSDMB expression was better than that of patients with low GSDMB expression. In vivo experiments showed that Anlotinib was more effective in the treatment of GSDMB-positive bladder cancer than GSDMB-negative bladder cancer. Anlotinib can increase the secretion of antitumor-related factors in GSDMB-positive bladder cancer such as TNF-a and CD107a. In addition, Anlotinib also induced an increase in GSDMB protein expression. Anlotinib treatment of GSDMB-positive bladder cancer decreased AKT and MEK protein expression, which were involved in Anlotinib signal transduction pathway.Conclusion: Anlotinib has a strong antitumor effect on GSDMB-positive bladder tumors. This effect is mainly achieved by anlotinib stimulating the secretion of relevant antitumor factors by lymphocytes. The PI3K/AKT and MEK signal transduction pathways were inhibited by Anlotinib in bladder cancer expressing GSDMB protein.Keywords: bladder cancer, Anlotinib, GSDMB, targeted therapy, pyroptosis